Evaluating a Multi-Disciplinary Response to Domestic Violence in Colorado Springs, 1996-1999 - Uchida, Craig D. ([Verlag nicht ermittelbar], 2002)
The Colorado Springs Police Department formed a nontraditional domestic violence unit in 1996 called the Domestic Violence Enhanced Response Team (DVERT). This unit involved a partnership and collaboration with the Center for the Prevention of Domestic Violence, a private, nonprofit victim advocacy organization, and 25 other city and county agencies. DVERT was unique in its focus on the safety of the victim over the arrest and prosecution of the batterer. It was also different from the traditional police model for a special unit because it was a systemic response to domestic violence situations that involved the coordination of criminal justice, social service, and community-based agencies. This study is an 18-month evaluation of the DVERT unit. It was designed to answer the following research and evaluation questions: (1) What were the activities of DVERT staff? (2) Who were the victims and perpetrators of domestic violence? (3) What were the characteristics of domestic violence-related incidents in Colorado Springs and surrounding jurisdictions? (4) What was the nature of the intervention and prevention activities of DVERT? (5) What were the effects of the intervention? (6) What was the nature and extent of the collaboration among criminal justice agencies, victim advocates, and city and county human services agencies? (7) What were the dynamics of the collaboration? and (8) How successful was the collaboration? At the time of this evaluation, the DVERT program focused on three levels of domestic violence situations: Level I included the most lethal situations in which a victim might be in serious danger, Level II included moderately lethal situations in which the victim was not in immediate danger, and Level III included lower lethality situations in which patrol officers engaged in problem-solving. Domestic violence situations came to the attention of DVERT through a variety of mechanisms. Most of the referrals came from the Center for the Prevention of Domestic Violence. Other referrals came from the Department of Human Services, the Humane Society, other law enforcement agencies, or city service agencies. Once a case was referred to DVERT, all relevant information concerning criminal and prosecution histories, advocacy, restraining orders, and human services documentation was researched by appropriate DVERT member agencies. Referral decisions were made on a weekly basis by a group of six to eight representatives from the partner agencies. From its inception in May 1996 to December 31, 1999, DVERT accepted 421 Level I cases and 541 Level II cases. Cases were closed or deactivated when DVERT staff believed that the client was safe from harm. Parts 1-4 contain data from 285 Level I DVERT cases that were closed between July 1, 1996, and December 31, 1999. Parts 5-8 contain data from 515 Level II cases from 1998 and 1999 only, because data were more complete in those two years. Data were collected from (1) police records of the perpetrator and victim, including calls for service, arrest reports, and criminal histories, (2) DVERT case files, and (3) Center for the Prevention of Domestic Violence files on victims. Coding sheets were developed to capture the information within these administrative documents. Part 1 includes data on whether the incident produced injuries or a risk to children, whether the victim, children, or animals were threatened, whether weapons were used, if there was stalking or sexual abuse, prior criminal history, and whether there was a violation of a restraining order. For Part 2 data were gathered on the date of case acceptance to the DVERT program and deactivation, if the offender was incarcerated, if the victim was in a new relationship or had moved out of the area, if the offender had moved or was in treatment, if the offender had completed a domestic violence class, and if the offender had served a sentence. Parts 3 and 4 contain information on the race, date of birth, gender, employment, and relationship to the victim or offender for the offenders and victims, respectively. Part 5 includes data on the history of emotional, physical, sexual, and child abuse, prior arrests, whether the victim took some type of action against the offender, whether substance abuse was involved, types of injuries that the victim sustained, whether medical care was necessary, whether a weapon was used, restraining order violations, and incidents of harassment, criminal trespassing, telephone threats, or kidnapping. Part 6 variables include whether the case was referred to and accepted in Level I and whether a DVERT advocate made contact on the case. Part 7 contains information on the offenders' race and gender. Part 8 includes data on the victims' date of birth, race, and gender.